Low-abrasiveness mesoporous zirconia ceramic for dental restoration and preparation method of low-abrasiveness mesoporous zirconia ceramic

By introducing mesoporous structures into dental zirconia ceramics, adjusting the mesoporous size and content, low abrasive mesoporous zirconia ceramics are prepared, which solves the problem of dental zirconia ceramics having strong abrasiveness to natural teeth, and achieves both good wear resistance and low abrasiveness of the ceramics.

CN119638413APending Publication Date: 2025-03-18SOUTHWEST JIAOTONG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411947852.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing dental zirconia ceramics are highly abrasive to natural teeth, resulting in severe wear of natural jaw teeth, and even causing serious iatrogenic damage such as natural root fractures and trauma in the occlusal system.

Method used

Mesoporous zirconia ceramics composed of tetragonal phase zirconia crystal particles are used, with a mesoporous size of 30-50 nm and a porosity of 0.3-20%. By regulating the pH value, ball milling time and sintering process of the ceramic slurry, low abrasive mesoporous zirconia ceramics are prepared.

Benefits of technology

While ensuring good wear resistance of ceramics, it can effectively reduce abrasion, reduce the risk of wear on natural teeth, and improve the safety and reliability of dental restoration materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638413A_ABST
    Figure CN119638413A_ABST
Patent Text Reader

Abstract

The invention discloses a low-abrasion mesoporous zirconia ceramic for dental restoration and a preparation method thereof, the mesoporous zirconia ceramic is composed of tetragonal phase zirconia crystal particles and has a mesoporous structure, the mesoporous size is 30-50nm, and the porosity is 0.3-20%; the preparation method mainly comprises the following steps: preparing a ceramic green body by a ceramic concentrated suspension liquid curing technology and sintering the ceramic green body. According to the mesoporous zirconia ceramic disclosed by the invention, mesopores are introduced among ceramic crystal particles, and the size and content of the mesopores are accurately regulated and controlled, so that good wear resistance of the material is ensured, and meanwhile, low abrasion of the material is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of ceramic oral restoration, and in particular relates to a low-abrasive mesoporous zirconia ceramic for dental restoration and a preparation method thereof. Background Art

[0002] Oral prosthesis is a type of implantable medical device used to repair and reconstruct the anatomical morphology and physiological function of missing natural human teeth. It is mainly made of zirconium oxide ceramics with excellent wear resistance, good biocompatibility and beautiful color. It is crucial to restore patients' chewing function and nutritional intake ability and improve their quality of life. There are a large number of patients with missing teeth in my country. The average number of missing teeth for people over 35 years old is 4.7. There are about 5 billion missing teeth in all age groups. China is one of the countries with the largest demand for zirconium oxide ceramic oral prostheses in the world.

[0003] After being implanted in the oral cavity, zirconia ceramic restorations directly contact and rub against the enamel of the outer layer of the opposing natural teeth. Therefore, an ideal ceramic oral restoration should have tribological properties that match human enamel, and should be wear-resistant without aggravating the wear of the opposing natural teeth. However, the wear resistance of the dental zirconia ceramics that have been used is much higher than that of human enamel, which leads to severe wear of the opposing natural teeth and even causes serious iatrogenic injuries such as natural tooth root fractures and occlusal system trauma. At present, research mainly prepares ceramic-based dental composites with lower stiffness and hardness by infiltrating resin polymers into porous ceramic frameworks to reduce the abrasiveness of the restorations on natural teeth. However, the introduction of resin polymers leads to excessive reduction in the wear resistance and strength of the restorations, significantly increasing the risk of premature wear failure and fracture damage, and there are hidden dangers such as easy aging and staining of the resin and adsorption of bacteria, which makes it difficult to meet clinical restoration needs. Summary of the invention

[0004] In order to solve the problem that existing dental zirconia ceramics have strong abrasiveness to natural teeth, the present invention provides a low-abrasive mesoporous zirconia ceramic for dental restoration and a preparation method thereof.

[0005] The low-abrasive mesoporous zirconia ceramic for dental restoration of the present invention is composed of tetragonal zirconia crystal particles, has a mesoporous structure, a mesopore size of 30 to 50 nm, and a porosity of 0.3 to 20%. The surface Vickers hardness of the mesoporous zirconia ceramic material is 800 to 1500 HV 50gf , the elastic modulus is 150~270Gpa.

[0006] The present invention provides a method for preparing a low-abrasive mesoporous zirconia ceramic for dental restoration, comprising the following steps:

[0007] Step 1: slurry preparation: weigh ceramic powder, citric acid monohydrate, and deionized water to prepare a ceramic slurry, wherein the ceramic powder content is 45-65wt%, the citric acid monohydrate content is 0.1-1wt%, and the balance is deionized water; adjust the pH value of the ceramic slurry to 7-10; use a planetary ball mill to fully mix the ceramic slurry, the ball milling time is 10-18h, and the rotation speed is 280-400r / min.

[0008] Step 2: Slurry coagulation: Weigh ammonium citrate and deionized water to prepare an ammonium citrate solution, wherein the ammonium citrate content is 10-15wt%; add 3-7ml of the ammonium citrate solution to the ceramic slurry, and stir with a magnetic stirrer for 1-2.5h.

[0009] Step 3: Slurry centrifugation: 3-4.5 ml of ceramic slurry is measured and injected into a centrifuge tube, and excess water in the slurry is separated by a centrifuge to obtain a zirconia ceramic wet embryo; a constant temperature and humidity chamber is preheated to a temperature of 35-60°C and a humidity of 60-80% RH, and the ceramic wet embryo is placed in the constant temperature and humidity chamber for about 5-10 hours; then, it is taken out and dried at room temperature for about 10-18 hours to obtain a zirconia ceramic dry embryo.

[0010] Step 4: Ceramic sintering: cold isostatic pressing the ceramic dry embryo; then place it in a silicon-molybdenum rod sintering furnace, heat it to 400-600°C, keep it warm for 0.5-1.5h, then continue to heat it to 1200-1500°C, keep it warm for 2-3h, and finally cool it to 300-500°C and cool it with the furnace to obtain mesoporous zirconia ceramics.

[0011] Furthermore, in step 1, the ceramic powder is composed of 85-90wt% zirconium dioxide powder, 5-10wt% aluminum oxide, 1-2wt% titanium dioxide, 1-2wt% silicon dioxide and 1-2wt% cerium dioxide nanoparticles, and the particle size is 30-100nm.

[0012] Furthermore, the zirconium dioxide powder is yttria-stabilized tetragonal zirconium dioxide crystal particles.

[0013] Furthermore, in step 1, the pH adjusting solution is an ammonia solution, and the ammonia concentration is 2 to 10 mol / L.

[0014] Furthermore, in step 3, the centrifugal speed is 6000-12000 r / min, and the centrifugal time is 10-20 min.

[0015] Furthermore, in step 4, the cold isostatic pressing is carried out at a pressure of 300 to 400 MPa for 5 to 10 minutes.

[0016] Furthermore, in step 4, the heating rate and the cooling rate during the sintering process are both 2 to 10° C. / min.

[0017] Beneficial technical effects of the present invention:

[0018] 1. The present invention proposes a new type of low-abrasive dental zirconia ceramic, which introduces mesopores between ceramic crystal particles and precisely controls the size and content of the mesopores, thereby achieving low abrasiveness of the ceramic while ensuring good wear resistance of the ceramic, and has great application prospects in the field of dental restorative materials.

[0019] 2. The present invention adopts the ceramic concentrated suspension solidification technology and prepares mesoporous zirconia ceramics by regulating the sintering process. The material preparation process provided by the present invention is simple and controllable, the required equipment is common equipment in the field, the raw materials used are cheap, non-toxic and pollution-free, and easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is an optical photograph of the low-abrasive mesoporous zirconia ceramic for dental restoration of the present invention.

[0021] Figure 2 This is a scanning electron microscope photograph of the low-abrasive mesoporous zirconia ceramic for dental restoration of the present invention.

[0022] Figure 3 The Vickers hardness and elastic modulus of the low-abrasive mesoporous zirconia ceramic for dental restoration of the present invention.

[0023] Figure 4 It is the friction coefficient of the surface of the low-abrasive mesoporous zirconia ceramic for dental restoration of the present invention.

[0024] Figure 5 The present invention provides the wear volume of the low-abrasive mesoporous zirconia ceramic for dental restoration and the surface of the friction pair talc porcelain ball thereof. DETAILED DESCRIPTION

[0025] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0026] Embodiment 1:

[0027] A method for preparing low-abrasive mesoporous zirconia ceramics for dental restoration comprises the following steps:

[0028] 1) Weigh 47 wt% of ceramic powder, 1 wt% of citric acid monohydrate, and 52 wt% of deionized water in a beaker to prepare a ceramic slurry, add an ammonia solution, and adjust the pH value to 8.

[0029] 2) The ceramic slurry was placed in a planetary ball mill and milled at a speed of 300 r / min for 12 h.

[0030] 3) Weigh 13 wt % ammonium citrate and 87 wt % deionized water to prepare an ammonium citrate solution, add 8 ml of the ammonium citrate solution to the ceramic slurry, and stir magnetically for 2 h.

[0031] 4) Pour 3 ml of the ceramic slurry into a 5 ml centrifuge tube. Use a centrifuge to separate excess water from the slurry at a centrifugal speed of 7000 r / min for 15 min. After centrifugation, remove the supernatant to obtain a ceramic wet embryo.

[0032] 5) Preheat the constant temperature and humidity chamber to 30° C. and 60% RH, place the wet ceramic embryo in the constant temperature and humidity chamber for 6 hours, and then take it out and dry it at room temperature for about 12 hours.

[0033] 6) The dried ceramic embryo is placed in a cold isostatic press and maintained at a pressure of 300 MPa for 6 minutes.

[0034] 7) The ceramic dry embryo is placed in a silicon-molybdenum rod sintering furnace, the temperature is raised to 400°C, kept at this temperature for 1 hour, then the temperature is further raised to 1250°C, kept at this temperature for 3 hours, and finally the temperature is lowered to 400°C and cooled with the furnace to obtain mesoporous zirconia ceramics; the heating rate and the cooling rate during the sintering process are both 5°C / min.

[0035] The optical photographs and scanning electron microscope photographs of the low-abrasive mesoporous zirconia ceramics for dental restoration prepared in this example are shown in FIG. Figure 1 and Figure 2 As shown, the mesoporous zirconia ceramic is milky white and mainly consists of nano-ceramic crystal particles 1. Mesopores 2 with a size of 30 to 45 nm exist between some of the crystal particles.

[0036] Performance Test:

[0037] 1) Surface hardness test: The Vickers hardness of the surface of low-abrasive mesoporous zirconia ceramics was tested using a KELITI000ZB microhardness tester (Sichuan Kelit Intelligent Technology Co., Ltd.), with a normal load of 50 gf and a holding time of 15 s.

[0038] The test results are as follows Figure 3 As shown: The Vickers hardness of the mesoporous zirconia ceramic surface is 1300HV 50gf , compared with commercial zirconia ceramics, the surface Vickers hardness of low abrasive mesoporous zirconia ceramics is reduced by about 20%.

[0039] 2) Elastic modulus test: The elastic modulus of low-abrasive mesoporous zirconia ceramics was tested using a G200 nanomechanical testing system (Keysight, USA). A Berkovich diamond indenter with a curvature radius of 20 nm was selected for the test, and the maximum indentation load was 50 mN.

[0040] The test results are as follows Figure 3As shown: The elastic modulus of mesoporous zirconia ceramics is 230 GPa. Compared with commercial zirconia ceramics, the elastic modulus of low abrasive mesoporous zirconia ceramics is reduced by about 16%.

[0041] 3) Reciprocating sliding friction and wear test: The tribological properties of low-abrasive mesoporous zirconia ceramics were tested using a UMT-TriboLab multifunctional friction and wear tester (Brook Company, USA). The test adopted a ball-plane contact mode, with a 4mm diameter steatite ceramic ball as the friction pair, a normal load of 3N, a reciprocating displacement of 1mm, a frequency of 5Hz, and a cycle number of 100,000 times.

[0042] The test results are as follows Figure 4 and Figure 5 As shown: Compared with commercial zirconia ceramics, the friction coefficient of the surface of low abrasive mesoporous zirconia ceramics is reduced by about 5%, the wear volume is increased by about 23%, and the wear volume of the surface of the talc ceramic ball of the friction pair is reduced by about 34%.

[0043] The mesoporous zirconia ceramic of the present invention effectively reduces abrasiveness while ensuring good wear resistance of the material by regulating the size and content of mesopores between ceramic crystal particles.

[0044] Embodiment 2:

[0045] A method for preparing low-abrasive mesoporous zirconia ceramics for dental restoration comprises the following steps:

[0046] 1) Weigh 47 wt% of ceramic powder, 1 wt% of citric acid monohydrate, and 52 wt% of deionized water in a beaker to prepare a ceramic slurry, add an ammonia solution, and adjust the pH value to 8.

[0047] 2) The ceramic slurry was placed in a planetary ball mill and milled at a speed of 300 r / min for 12 h.

[0048] 3) Weigh 13 wt % ammonium citrate and 87 wt % deionized water to prepare an ammonium citrate solution, add 8 ml of the ammonium citrate solution to the ceramic slurry, and stir magnetically for 2 h.

[0049] 4) Pour 3 ml of the ceramic slurry into a 5 ml centrifuge tube. Use a centrifuge to separate excess water from the slurry at a centrifugal speed of 7000 r / min for 15 min. After centrifugation, remove the supernatant to obtain a ceramic wet embryo.

[0050] 5) Preheat the constant temperature and humidity chamber to 30° C. and 60% RH, place the wet ceramic embryo in the constant temperature and humidity chamber for 6 hours, and then take it out and dry it at room temperature for about 12 hours.

[0051] 6) The dried ceramic embryo is placed in a cold isostatic press and maintained at a pressure of 300 MPa for 6 minutes.

[0052] 7) The ceramic dry embryo is placed in a silicon-molybdenum rod sintering furnace, the temperature is raised to 300°C, kept at this temperature for 1 hour, then the temperature is further raised to 1230°C, kept at this temperature for 2 hours, and finally the temperature is lowered to 400°C and cooled with the furnace to obtain mesoporous zirconia ceramics; the heating rate and the cooling rate during the sintering process are both 5°C / min.

[0053] The low-abrasive mesoporous zirconia ceramic for dental restoration prepared in this embodiment is mainly composed of nano-ceramic crystal particles, and mesopores with a size of 40 to 50 nm exist between some of the crystal particles.

[0054] Performance Test:

[0055] 1) Surface hardness test: The Vickers hardness of the surface of low-abrasive mesoporous zirconia ceramics was tested using a KELITI000ZB microhardness tester (Sichuan Kelit Intelligent Technology Co., Ltd.), with a normal load of 50 gf and a holding time of 15 s.

[0056] The test results show that the surface Vickers hardness of mesoporous zirconia ceramics is 1200HV 50gf , compared with commercial zirconia ceramics, the surface Vickers hardness of low abrasive mesoporous zirconia ceramics is reduced by about 26%.

[0057] 2) Elastic modulus test: The elastic modulus of low-abrasive mesoporous zirconia ceramics was tested using a G200 nanomechanical testing system (Keysight, USA). A Berkovich diamond indenter with a curvature radius of 20 nm was selected for the test, and the maximum indentation load was 50 mN.

[0058] The test results show that the elastic modulus of the mesoporous zirconia ceramics is 215 GPa. Compared with commercial zirconia ceramics, the elastic modulus of the low-abrasive mesoporous zirconia ceramics is reduced by about 21%.

[0059] 3) Reciprocating sliding friction and wear test: The tribological properties of low-abrasive mesoporous zirconia ceramics were tested using a UMT-TriboLab multifunctional friction and wear tester (Brook Company, USA). The test adopted a ball-plane contact mode, with a 4mm diameter steatite ceramic ball as the friction pair, a normal load of 3N, a reciprocating displacement of 1mm, a frequency of 5Hz, and a cycle number of 100,000 times.

[0060] The test results show that compared with commercial zirconia ceramics, the surface friction coefficient of low-abrasive mesoporous zirconia ceramics is reduced by about 3%, the wear volume is increased by about 35%, and the wear volume of the talc ceramic ball surface of the friction pair is reduced by about 20%.

[0061] The mesoporous zirconia ceramic of the present invention effectively reduces abrasiveness while ensuring good wear resistance of the material by regulating the size and content of mesopores between ceramic crystal particles.

[0062] In summary, the present invention is based on the solidification technology of ceramic concentrated suspension, and a mesoporous zirconia ceramic is prepared by regulating the sintering process. The preparation process is simple and controllable, the required equipment is common equipment in the field, the raw materials used are cheap, non-toxic and pollution-free, and it is easy to mass produce. At the same time, the mesoporous zirconia ceramic of the present invention has both good wear resistance and low abrasiveness, overcoming the bottleneck problem of strong abrasiveness of traditional dental zirconia ceramics, and has great application prospects in the field of dental restorative materials.

Claims

1. A low-abrasive mesoporous zirconia ceramic for dental restoration, characterized in that: It is composed of tetragonal zirconium oxide crystal particles and has a mesoporous structure. The mesopore size is 30-50nm and the porosity is 0.3-20%. The surface Vickers hardness of the mesoporous zirconium oxide ceramic material is 800-1500HV. 50gf , the elastic modulus is 150~270Gpa.

2. The method for preparing a low-abrasive mesoporous zirconia ceramic for dental restoration according to claim 1, characterized in that: The following steps are involved: Step 1: Slurry preparation: Weigh ceramic powder, citric acid monohydrate, and deionized water to prepare a ceramic slurry, wherein the ceramic powder content is 45-65wt%, the citric acid monohydrate content is 0.1-1wt%, and the balance is deionized water; adjust the pH value of the ceramic slurry to 7-10; use a planetary ball mill to fully mix the ceramic slurry, the ball milling time is 10-18h, and the rotation speed is 280-400r / min; Step 2: Slurry coagulation: Weigh ammonium citrate and deionized water to prepare an ammonium citrate solution, wherein the ammonium citrate content is 10-15wt%; add 3-7ml of the ammonium citrate solution to the ceramic slurry, and stir with a magnetic stirrer for 1-2.5h; Step 3: Slurry centrifugation: 3-4.5 ml of ceramic slurry is measured and injected into a centrifuge tube, and excess water in the slurry is separated by a centrifuge to obtain a wet zirconia ceramic embryo; a constant temperature and humidity chamber is preheated to a temperature of 35-60° C. and a humidity of 60-80% RH, and the wet ceramic embryo is placed in the constant temperature and humidity chamber for about 5-10 hours; then, the wet ceramic embryo is taken out and dried at room temperature for about 10-18 hours to obtain a dry zirconia ceramic embryo; Step 4: Ceramic sintering: cold isostatic pressing the ceramic dry embryo; then place it in a silicon-molybdenum rod sintering furnace, heat it to 400-600°C, keep it warm for 0.5-1.5h, then continue to heat it to 1200-1500°C, keep it warm for 2-3h, and finally cool it to 300-500°C and cool it with the furnace to obtain mesoporous zirconia ceramics.

3. The method for preparing a low-abrasive mesoporous zirconia ceramic for dental restoration according to claim 2, characterized in that: The ceramic powder in step 1 is composed of 85-90wt% zirconium dioxide powder, 5-10wt% aluminum oxide, 1-2wt% titanium dioxide, 1-2wt% silicon dioxide and 1-2wt% cerium dioxide nanoparticles, and the particle size is 30-100nm.

4. The method for preparing a low-abrasive mesoporous zirconia ceramic for dental restoration according to claim 3, characterized in that: The zirconium dioxide powder is tetragonal zirconium dioxide crystal particles stabilized by yttria.

5. The method for preparing a low-abrasive mesoporous zirconia ceramic for dental restoration according to claim 2, characterized in that: The pH adjusting solution in step 1 is an ammonia solution with an ammonia concentration of 2 to 10 mol / L.

6. The method for preparing a low-abrasive mesoporous zirconia ceramic for dental restoration according to claim 2, characterized in that: In step 3, the centrifugal speed is 6000-12000 r / min, and the centrifugal time is 10-20 min.

7. The method for preparing a low-abrasive mesoporous zirconia ceramic for dental restoration according to claim 2, characterized in that: In step 4, the cold isostatic pressing is carried out at a pressure of 300 to 400 MPa for 5 to 10 minutes.

8. The method for preparing a low-abrasive mesoporous zirconia ceramic for dental restoration according to claim 2, characterized in that: The heating rate and cooling rate during the sintering process in step 4 are both 2-10° C. / min.

Citation Information

Cited By

  • Amorphous zirconia dental restoration material and preparation method thereof

    CN120788921A